(3GdeYOf GdYOfi aj aVd ChjS GdbQfis - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s; (3CMeO Hf eMeO GdfjSGHhQjs
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg eG HYO ajbhd Cf gPg ebGdI eTJedI Ydi HjGf aVGFd MjR GdJGHYjf s
(3BNQgG (B:s
(3QRbfG Gddg GdRjGOI GdeaSQI HGddbG ai ebGe GdMSfi hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B26s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B136) s
Keywords: (3GdeLGejYs